Framing Social Theory Reassembling the Lexicon of Contemporary Social Sciences - Rebughini, Paola; colombo, enzo (Routledge Advances in Sociology, 2023)
This book proposes a reconstruction of contemporary social theory, focusing on thematic issues rather than on authors or schools of thought. In so doing, it endeavours to bridge epistemological approaches and locate critical claims shared by the main trajectories and notions of sociological theoretical debate. The book explores the current forms of social science theorization through the key themes of Agency, Anthropocene, Coloniality, Intersectionality, Othering, Singularization, Technoscience and Uncertainty. Focusing on these key themes, it highlights their usefulness for discussions of inequality, neoliberalism, eurocentrism, androcentrism or anthropocentrism - in order to examine these issues in a new light and look beyond the classic divides of social theory. Intended for an academic audience interested in social theory, scholars and post-graduate students in sociology, social sciences, anthropology, social geography, social psychology and globalization studies will find this book useful. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.